Transcriptional regulation of the Ikzf1 locus - Yoshida, Toshimi (American Society of Hematology, 2013)
Ikaros is a critical regulator of lymphocyte development and homeostasis; thus, understanding its transcriptional regulation is important from both developmental and clinical perspectives. Using a mouse transgenic reporter approach, we functionally characterized a network of highly conserved cis-acting elements at the Ikzf1 locus. We attribute B-cell and myeloid but not T-cell specificity to the main Ikzf1 promoter. Although this promoter was unable to counter local chromatin silencing effects, each of the 6 highly conserved Ikzf1 intronic enhancers alleviated silencing. Working together, the Ikzf1 enhancers provided locus control region activity, allowing reporter expression in a position and copy-independent manner. Only 1 of the Ikzf1 enhancers was responsible for the progressive upregulation of Ikaros expression from hematopoietic stem cells to lymphoid-primed multipotent progenitors to T-cell precursors, which are stages of differentiation dependent on Ikaros for normal outcome. Thus, Ikzf1 is regulated by both epigenetic and transcriptional factors that target its enhancers in both redundant and specific fashions to provide an expression profile supportive of normal lymphoid lineage progression and homeostasis. Mutations in the Ikzf1 regulatory elements and their interacting factors are likely to have adverse effects on lymphopoiesis and contribute to leukemogenesis.